A Weed Population Dynamics Model for Integrated Weed-Management Decision-Making Support: Euphorbia davidii Subils in Soybean Crops as a Simulation Study - Franco A. Molinari; Aníbal M. Blanco; Federico R. Núñez Fré; Víctor F. Juan; Guillermo R. Chantre (Agronomy, 2022)
A crop–weed simulation model is presented to compare and evaluate integrated weed-management (IWM) strategies. Specifically, the model was parameterized for soybean crops in competition with Euphorbia davidii Subils. We used both weed and crop demographic data surveyed in agronomic fields of the central zone of the Buenos Aires province, Argentina, throughout two crop cycles (2011/2012 and 2013/2014). The proposed model underwent a calibration process and subsequent validation with a 70/30% data split, (N = 37). Two annual-based and one multiannual-based case studies were simulated to demonstrate the performance of the model. Different IWM strategies were compared under both operational and tactical planning horizons through the evaluation of different model outcomes (i.e., crop yield, interspecific competition, economic return, and environmental impact). Our results suggest that the inclusion of cultural management practices could reduce both weed interspecific competition by 46 to 97%, and weed seed production by 40 to 89 %. An increment in both expected crop yield, by 6 to 20%, and annual gross margin, by 44 to 199 USD.ha−1, were obtained in silico for similar levels of environmental impact.